Gleanings From Brhat Sumhita in Context of Plant Invasion in India - Patil, Dinkarrao Amrutrao (Plantae Scientia, 2024)
This communication informs exotic plant species as gleaned from Varahamihira's (505-587 AD) Brhat Samhita. The said treatise contains plant species of medicinal significance and also those used for miscellaneous purposes. The present author critically analysed their Sanskrit plant names and equated with recent botanical (Latin) names assigning to their respective families. They are deciphered for their exotic status consulting relevant taxonomic literature. Brhat Samhita contains information on total 273 plant species for various uses. Out of these, as many as 77 exotic plant species pertaining to 73 genera and 38 angiospermic families. Their categorization based on habit is also proposed along with their status regarding wildness or as cultigens. It is hoped that such studies on plant invasion in ancient period of India many help add in the history of bioinvasion and also useful in the considerations of biodiversity management and its conservation measures in future.